TRAJECTORIES OF THE ECONOMIC STATEOF THE RUSSIAN FEDERATION AND THE USA IN 2001-2015 - Chechulin, V.L.; Lopatin, A.A. (Perm Federal Research Centre Journal, 2016)
In the article the trajectories of economic state of the Russian Federation and the USA economies in the years 2001 to 2015 constructed by means of model of non-inflationary economy state are described. It is specified that since 2009 till present time the USA economy has been passing the area of unsustainability.